Integration of Bayani, Burhani and Irfani Epistemologies in Arabic Language Learning in Islamic Boarding School-Based Colleges - Amirul Mukminin; Hanun, Aisyatul; Zainuddin; Mushtofa , Lutfi; Wassalwa, Almannah (Asalibuna, 2025)
This study aims to explore the integration of three Islamic epistemological approaches—Bayani, Burhani, and Irfani—in Arabic language education. These approaches represent distinct yet complementary sources and methods of acquiring knowledge, collectively contributing to the development of a holistic and meaningful instructional model. The Bayani approach emphasizes textual interpretation based on authoritative sources and classical scholarly traditions; the Burhani approach prioritizes logic and rational analysis; while the Irfani approach centers on intuition, spiritual depth, and inner experience. Through a literature review of philosophical and Arabic language education sources, this study finds that the current dominance of the grammatical approach in Arabic instruction has led to a fragmentation of meaning and a disconnection from the philosophical and spiritual dimensions of the language. Integrating these three epistemological perspectives not only strengthens learners’ linguistic competencies but also cultivates critical thinking and spiritual awareness of language as a divine medium. This research proposes an epistemological synthesis model as an alternative pedagogical framework for a more contextual, reflective, and transformative Arabic language learning experience.